“DESAIN USER INTERFACE PADA SHOFA MOM, KIDS AND BABY SPA MASSAGE” - aji, Rahmat Perdana Aji; Henny Lukitasari, Evelyne; Wibowo, Yudi (Universitas Sahid Surakarta, 2024)
Abstract The development of baby spa in the Indonesian business sector is very large and creates good business opportunities. This is because of the many benefits of a baby spa. One of the baby spas is Shofa Moms and Baby Spa in Sukoharjo. Shofa Moms and Baby Spa provides treatment services such as baby massage with complaints, a baby gym and nursing care. Shofa Moms and Baby Spa has a special treatment using natural oils. The treatment facilities are waiting rooms with air conditioning, the availability of wifi makes customers comfortable waiting and carrying out their treatments. In the development era of businesses being better known to the wider market reach, the use of the internet as a tool for introducing its services to consumers will be more effective and efficient. It is because information needs are easy to obtain. However, the use of the same online media and the many online media owned makes business competition in the online media and ordering services ineffective due to the different online media platforms. Shofa Mom, Kids and Baby Spa Massage also uses the same online media as competitor baby spa in the Sukoharjo area. Therefore, Shofa Mom, Kids and Baby Spa Massage experienced a decline in sales. Shofa Mom, Kids and Baby Spa Massage must have different and effective online media in ordering and promoting its services. Thus, the User Interface design of Shofa Mom, Kids and Baby Spa Massage is made using the visual branding design method with qualitative data collection. The results obtained are the creation of the User Interface design into a new effective online media because the creation of the Shofa Mom, Kids and Baby Spa Massage website is attractive in the ease of finding information and promotions, and makes it easier when ordering services at Shofa Mom, Kids and Baby Spa Massage in one online media platform. Keywords: Spa, Mom, Kids, and Baby Spa Massage, User Interface